Crypto Visual Culture and Participation in Platform Based Creative Economies (Open Society Conference, 2025)
This study examined the role of visual design in Non-Fungible Tokens (NFTs) as a strategic component of value creation and inclusive participation within the decentralized creative economy. The research addressed the growing need to understand how visuals influence identity, accessibility, and community-driven economic engagement in digital platforms. The study was conducted using a qualitative interpretive approach, employing visual rhetorical analysis and digital ethnography. Ten top NFT collections on the OpenSea marketplace were analyzed based on their visual characteristics, creator inclusion, and community interaction. The visual elements were assessed through rhetorical lenses ethos, pathos, and logos, while participation was observed through social media metrics and community discourse. The findings indicated that accessible and culturally resonant visual designs enhanced user engagement and contributed to broader economic inclusion. Collections with visually open, emotionally engaging, and culturally inclusive features attracted stronger community involvement and sustained market relevance. In contrast, NFTs with elitist or exclusive visual narratives demonstrated more limited participation and accessibility. The study concluded that visual identity plays a central role in shaping the success of NFTs not only as aesthetic artifacts but as instruments of economic democratization. It was recommended that future research explore algorithmic visual production and long-term community dynamics across diverse cultural contexts. This research highlighted the potential of visual design to foster equity, representation, and sustainable value in the evolving digital economy.